Unveiling the room-temperature chemiresistive NH3 adsorption capability of NiO doped PPy nanocomposite with DFT interpretations - Ratindra Gautam; Shivani Chaudhary; Vivek Kumar Nautiyal; Bal Chandra Yadav; Utkarsh Kumar (Nano Express)
The responsive and selective identification of ammonia at room temperature is crucial for effective environmental pollution control and for preventing health hazards in industrial settings. The excellent electrical properties of nickel (Ni) and the sensing capabilities of polypyrrole (PPy) have been synergistically combined to achieve enhanced ammonia sensitivity. NiO-doped PPy nanoparticles were synthesized via an oxidative polymerization route, and the resulting nanomaterials were thoroughly characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), and UV-visible spectroscopy. The bandgap, determined from UV-visible spectroscopy data, was found to be 4.6 eV. The sensor exhibited a maximum response of 0.29 at 225 ppm of NH _3 , with minimum response and recovery times of 11 s and 18 s, respectively. The limit of detection has been calculated by using the linear curve fitting of sensor response and found to be 17.31 ppm. Density Functional Theory (DFT) simulations were employed to investigate the adsorption of NH _3 molecules on NiO-doped PPy nanoparticles. The simulations revealed changes in dipole moment, adsorption energy, and HOMO–LUMO gaps upon NH _3 adsorption. Additionally, Density of States (DOS) plots indicated alterations in the composition of the HOMO–LUMO levels due to NH _3 adsorption. This study demonstrates the potential of NiO-doped PPy nanoparticles as highly responsive and selective ammonia gas sensors, providing rapid detection and reliable performance at room temperature.